SOLVE ONE-DIMENSIONAL OPTIMIZATION PROBLEMS USING NEWTON-RAPHSON METHOD - Mungkala, C.; Bunpatcharacharoen, P.; Janwised, J. (Journal of Nonlinear Analysis and Optimization: Theory & Applications (JNAO), 2017)
This research studied solve one-dimensional optimization problems using Newton – Raphson Method. This method uses first derivatives to solve solutions. It was tested with 12 function tests and tested the efficiency of the solution convergence rate Newton – Raphson method and the random search method. It was found that the Newton-Raphson method was more effective in converging rate to better answers than random search methods. The error value and the iteration are indicative.